Future Challenges for School Leaders in Implementing the Concept of Learning Organizations in Malaysian Schools: Experts’ Opinions - Ishak, Rosnah (International Journal of Advanced Corporate Learning (iJAC), 2020)
Based on the idea of learning organization, schools should be a place for everyone to learn, including teachers and the principals themselves. Hence, schools’ leaders should be prepared to face various possibilities in implementing the concept of learning organization in school. This paper discuss about a study aims to identify future challenges for school principals as leaders in learning organizations. A total of eight school principals have been appointed as panel of experts and involved in a focus group discussion. The results from qualitative data analysis show that there are seven main elements forecast to be the challenges for school leaders in developing their schools as learning organizations in future. The implications of the study suggest that school leaders apply a variety of leadership skills as a result of their learning to overcome those challenges.